Primary angiosarcoma of the vulva: report of a case misdiagnosed as a benign tumor - Stolnicu, Simona; Podoleanu, Cristian; Orban, Ildiko; Stan, Octavian; Szabo, Bela (Polish Journal of Pathology, 2021)
Primary vulvar angiosarcomas have a propensity for varied macroscopic and histologic appearance that initially may not suggest a vascular malignant neoplasm. Therefore, the rarity of the lesion and it’s morphologic diversity may contribute to the high rate of misdiagnosis. We present the case of a 43-year old patient with a primary vulvar lesion, initially misdiagnosed as an angiofibroma. Microscopic examination of the recurrence together with immunohistochemical profile were in favor on a poorly differentiated angiosarcoma. Early diagnoses can improve prognoses in angiosarcomas and, in the case of recurrences, as in the present case, may lead to changes in therapy.